Exophytic gastric leiomyoma with retroperitoneal growth - A. Praderi, Luis; Maquieira, Gonzalo; F. Cassinelli, Juan (Cirugía del Uruguay, 1971)
A rare gastric tumor, the leiomyoma with very large exophitic growth, has the appearence of large retroperitoneal tumors. It is a gastric tumor and presents no symptoms on the viscus on which it is appended; causing only sub-occlusion of colon. Radiologically, it is an opaque tumor, of the retrocavity, corresponding to the area of the body of the pancreas and extends upwards opening the left colic angle, instead of closing it. It is a rare lesional association of a slow-growth gastric tumor and acute lithiasic cholecystitis in the perforative stage, which explains the infectious syndrone and simulates a secondary liver. The patient was informed of the existence of a benign tumor so as to prepare him for the second, more serious, operation. Was treated with two-step surgery; the first, septic; the second with unavoidable colonic resection due to involvement of its nutrional vessels. The tumor is histologically benign but due to is vascular damage (and eventual metastases) it is decided to classify it as a leiomyosarcoma withreserved prognosis.